2018
DOI: 10.1111/ijd.14174
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and mortality outcome in the drug reaction with eosinophilia and systemic symptoms patients with cardiac involvement

Abstract: Our study showed the prevalence of CiDs was as high as 19.5% with high mortality rate. We suggest a thorough cardiac evaluation in all DRESS patients with RegiSCAR score ≥4. The patients with CiDs had significantly lower hemoglobin and albumin levels, which might imply poor health condition, when compared to those without CiDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
(53 reference statements)
2
18
1
Order By: Relevance
“…The general consensus is that DS has no sex predilections. Some studies reported female predominance [57,58], while others reported DS being more common in the male population [7]. Our data showed female predominance (61.9%), but mortality was not associated with gender.…”
Section: Age and Sexcontrasting
confidence: 43%
See 2 more Smart Citations
“…The general consensus is that DS has no sex predilections. Some studies reported female predominance [57,58], while others reported DS being more common in the male population [7]. Our data showed female predominance (61.9%), but mortality was not associated with gender.…”
Section: Age and Sexcontrasting
confidence: 43%
“…Prior studies of DS have reported a relatively low incidence of cardiac involvement in DRESS (11 of 83 patients, 13.3%): Intarasupht et al [7] described cardiac manifestations in 8 out of 41 patients (20%) diagnosed with DS in Bangkok, Thailand hospital over a 5-year period; Eshki et al [36] conducted a retrospective study in France over the span of 12 years and found cardiac involvement in only 2 out 15 patients (13%) diagnosed with DS; Ang et al [49] reported only 1 case of myocarditis out of 27 analyzed patients (4%) diagnosed with DIHS over a 5-year period in Singapore hospital.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Norepinephrine and dobutamine were completely withdrawn, while milrinone was intentionally fixed at a low dose. Overall, the most common arrhythmias were sinus tachycardia and right bundle branch block ( Table 2), [5][6][7][8][9]11,12,14,[16][17][18][21][22][23][25][26][27][28][29][30]32,[37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53] usually appearing as initial rhythms on admission. On the contrary, ventricular arrhythmias and complete heart block mostly happened late in the clinical course.…”
Section: Case Presentationmentioning
confidence: 99%
“…By searching the PubMed database using the keywords 'DRESS' or 'drug-induced hypersensitivity syndrome' and 'myocarditis', as of August 2020, we identified 63 reported cases of DRESS-associated myocarditis in the literature: 43 case reports, four case series, 48-51 and three small observational studies [52][53][54]. The incidence of DRESS-associated myocarditis ranged from one to five cases per year(Figure 3).…”
mentioning
confidence: 99%